Comparative Pharmacokinetics/Pharmacodynamic Modeling on Three Brands of 10% Enrofloxacin Oral Formulations in Broiler Chickens - Gberindyer, Fidelis Aondover; Wannang, Noel; Akwuobu, Chinedu Adive (International Journal of Poultry Science, 2010)
A comparative plasma pharmacokinetics/Pharmacodynamic modeling of enrofloxacin following administration of three brands of 10% enrofloxacin was studied in healthy broiler chickens using a randomized and parallel design. Pre-treatment and post-treatment samples were obtained from brachial or right jugular veins after having administered 20 mg/kg b.w of enrofloxacin at 0, 0.5, 1, 2, 3, 4, 6, 8, 10, 12 and 24 h. Plasma samples were analyzed for enrofloxacin concentration by a simple agar disk diffusion microbiological assay. Selected pharmacokinetics parameters were calculated using a non-compartmental model. There was a significant difference in the plasma concentration-time and pharmacokinetics profiles (p<0.05) of the three brands. But the plasma concentrations of enrofloxacin exceeded the MIC90 for most pathogenic bacterial organisms in poultry in all the groups. The PK/PD integration (Cmax/MIC90) values, 16.67, 15.17 and 10.5 h were obtained in animals administered conflox®-vet, kenflox® and pulmotryl® formulations respectively. This correlates with high efficacy and reduced chances for the development of resistant pathogenic bacterial organisms following oral administration of these brands of enrofloxacin oral formulations in broiler chickens.